SIFAT-SIFAT RING FAKTOR YANG DILENGKAPI DERIVASI - Iwan Ernanto (Journal of Fundamental Mathematics and Applications (JFMA), 2018)
Let $R$ is a ring with unit element and $δ$ is a derivation on $R$. An ideal $I$ of $R$ is called $δ$-ideal if it satisfies $δ (I)\subseteq I$. Related to the theory of ideal, we can define prime $δ$-ideal and maximal $δ$-ideal. The ring $R$ is called $δ$-simple if $R$ is non-zero and the only $δ$-ideal of $R$ are ${0}$ and $R$. In this paper, given the necessary and sufficient conditions for quotient ring $R/I$ is a $δ$-simple where $δ_*$ is a derivation on $R/I$ such that $δ_* ° π =π ° δ$.